Household Welfare and Natural Resource Management around National Parks in Zambia - Bandyopadhyay, Sushenjit; Tembo, Gelson (2012)
Game management areas in Zambia aim to combine nature conservation with economic empowerment of rural households. By looking at households inside and outside game management areas, this study advances the knowledge of the impact of community based natural resource management on household welfare. The paper focuses on the economic welfare of households living inside game management areas. It tries to answer the question: Do the households in game management areas enjoy higher levels of welfare relative to the conditions they would have been in had the area not been designated as a game management area? Within the game management area, the paper tries to determine the factors that influence household participation in natural resource management, and whether the participating households get any extra benefits. Also of interest is whether such benefits of living in a game management area, and, once in such an area, those of participating accrue more to the poorer segments of the communities. The study finds that the gains from living in a game management area and from active participation in natural resource management are large but unevenly distributed. Only game management areas near Kasanka, Lavushi, Isangano, and South Luangwa national parks in the sample show significant benefits to general and participating households. And in those areas, the poor do not seem to gain even when they participate actively. More even distribution of gains from game management areas across households near different park systems and across the poor and the non-poor should be a continuing goal of national policy makers.